The Urgency of Establishing Village Customary Institutions as Legal Protection for Local Culture: An Empirical Study in Bojonegoro Regency - Purwanto, Gunawan Hadi; Yasir, M.; Rahmania, Cindy Swastika (Universitas Internasional Batam, 2025)
The rapid development of society, driven by globalization and modernization, poses significant challenges to the preservation of local culture and identity. This study addresses a critical legal issue: the absence of village customary institutions across most villages in Bojonegoro Regency, despite their legal basis under Article 95 Paragraph (1) of Law Number 6 of 2014 on Villages. The research aims to explore the legal urgency and practical necessity of establishing village customary institutions as institutional mechanisms to safeguard cultural heritage and customary law within rural communities. Using an empirical legal research approach, this study investigates real-world legal practices through structured interviews with village authorities in Trucuk Village—currently the only village in Bojonegoro Regency with a formally established village customary institutions. The data were analyzed using qualitative descriptive methods to assess the institutional, legal, and sociocultural implications. Findings reveal that the village customary institutions in Trucuk Village functions not only as a legal instrument for preserving cultural values and indigenous traditions but also as a mediator in local dispute resolution, a protector of communal rights, and a catalyst for community-based cultural and economic development. The absence of such institutions in 418 other villages signals a significant gap in the implementation of village autonomy and cultural protection policies. This research highlights the urgent need for local governments to align with national legal mandates by promoting the establishment of village customary institutions as legally recognized entities. Doing so will reinforce local identity, strengthen community governance, and serve as a legal bulwark against cultural erosion. The study calls for policy-level awareness and coordinated action to replicate Trucuk’s model throughout the region.